Isolation, characterisation and technological properties of raw donkey's milk isolate, Lacticaseibacillus paracasei, compared to raw goat's and cow's milk isolates - Gabriela Greifová; Eva Drobná; Petra Olejníková; Gabriel Greif; Mária Greifová (Czech Journal of Food Sciences)
Donkey milk is a very promising matrix for the isolation of new potential starter cultures with probiotic properties. We isolated, identified, and compared the technological properties of the donkey milk isolate D23 with those of goat milk isolates G15 and G17 and bovine milk isolates C3 and C9. All isolates were identified as Lacticaseibacillus paracasei using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF-MS) and polymerase chain reaction (PCR) assays (determination of species-specific DNA fragments). Like the bovine and goat isolates, the donkey milk isolate D23 was able to grow in De Man-Rogosa-Sharpe (MRS) broth at various temperatures (10, 25, 30, 37, and 45 °C) and at different NaCl concentrations (0-6.5% w/v). Additionally, D23 showed notable proteolytic and autolytic activity, could grow in and acidifying ultra high temperature (UHT) bovine milk but exhibited very weak diacetyl production. None of the isolates displayed hemolytic activity, nor produced histamine, fenylethylamine and cadaverine. Finally, isolate D23 demonstrated interesting antibacterial and antifungal properties compared to the goat and bovine isolates, especially against staphylococcus aureus CCM 3953.